COMMON MICROFLORA INVOLVED IN SPOILAGE OF CANNED PRAWNS - NAMBIAR, V NARAYANAN; IYER, K MAHADEVA (Fishery Technology, 2025)
An elaborate survey was carried out to ascertain the commontypes of micro-organisms responsible for spoilage in canned prawns.Among nearly 1,500 strains isolated from bacteriologically defectivecans, 60% were Gram positive sporeformers of the Bacillus type.Other types Â·'solated belonged to Gram positive cocci, Gram negativerods, Gram positive non:::sporeforming rods, Gram negative cocci andcoccoids. No anaerobe could be isolated. The predominant. Grampositive sporeformers were identified as Bacillus pantothenlicus,B. {lrmusJ B. brevis and B. Pumilus species.